2019
DOI: 10.14475/kjhpc.2019.22.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Death Anxiety in Community-Dwelling Elderly: Based on the Ecology Theory

Abstract: This study analyzed a path through which factors influencing death anxiety in the community-dwelling elderly, assuming personal organismic factors and microsystemic factors based on the ecology model purported by Belsky (1980). Methods: This study was performed with 189 elderly people. Data were collected through a self-report questionnaire. The data were analyzed using the SPSS and AMOS programs. Results: The factors influencing death anxiety in the elderly were depression, family support, social network, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
2
1
1
Order By: Relevance
“…These results are in agreement with other studies done in India by Singh (2013), in USA by Assari & Moghani Lankarani (2016), in Korea by Kwon & Kim (2016) and in Egypt, Alex by Sebea et al, (2021) who revealed that there was a significant relation between age and death anxiety. The result of the present study contradicts those reported by Kim (2019) and Hassan et al, (2019) who demonstrated that age was not associated with death anxiety.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with other studies done in India by Singh (2013), in USA by Assari & Moghani Lankarani (2016), in Korea by Kwon & Kim (2016) and in Egypt, Alex by Sebea et al, (2021) who revealed that there was a significant relation between age and death anxiety. The result of the present study contradicts those reported by Kim (2019) and Hassan et al, (2019) who demonstrated that age was not associated with death anxiety.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are in accordance with previous studies which demonstrated that death anxiety level is higher in women than men (Kim et al, 2010;Singh, 2013;Taghipour, et al, 2017;Ghasemi, et al, 2020). Conversely, other studies found that there was no significant difference in death anxiety between men and women ( Assari&Lankarani, 2016;Kim, 2019;Sebea et al, 2021). Also, another study conducted in Jordan by Rababa et al, (2021) revealed that elderly men had higher mean score of death anxiety than women with significant difference in death anxiety between men and women.…”
Section: Discussionsupporting
confidence: 91%
“…Momtaz et al (2010) suggested that the death of significant others, especially the loss of a spouse, is one of the most difficult times faced by elderly people. Besides, the feeling of depression, lack of family support, poor social network and decreased familial values enhance the elderly death anxiety (Kim and Kim, 2019). Moreover, elderly experiences of loneliness are associated with health-related risk and negative well-being (Wong et al, 2017), which highly influence their psychological well-being as well (Lim and Kua, 2011).…”
Section: Loneliness and Death Anxietymentioning
confidence: 99%
“…The fact that everyone will inevitably face death at one point in life can cause significant stress and anxiety in individuals (2). The anxiety about one's own death might manifest in some individuals as a continuous and abnormal fear (3). This anxiety, as the initial component of death, includes a whole host of personal views, such as general fear, threat, worries, sense of discomfort, and other stressful reactions (4).…”
Section: Introductionmentioning
confidence: 99%